2017
DOI: 10.1177/1471301217700965
|View full text |Cite
|
Sign up to set email alerts
|

Young Adults’ Concerns and Coping Strategies Related to their Interactions with their Grandparents and Great-Grandparents with Dementia

Abstract: Young adults' concerns and coping strategies related to their face-to-face interactions with their grandparents/great-grandparents with dementia were explored through the lens of a solidarity-conflict conceptual framework. Participants indicated concerns about their inability to maintain the relational connection, not knowing what to say or how to behave, their lack of perspective-taking skills and emotion-regulation strategies, interacting with an ever-changing other, as well as concerns about other co-partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(48 citation statements)
references
References 43 publications
1
47
0
Order By: Relevance
“…Previous research identified some of the GDs' concerns; for example, it was found that GCs worry about the health of their GP (Boon et al, 2008) and that they do not possess the skills needed to create an alternative interaction with a GP suffering from dementia (Miron et al, 2019). The present research expands these insights and stresses that concern about successfully creating meaningful interaction is also shared by 30-to 45-year-old GCs.…”
Section: Discussionmentioning
confidence: 54%
See 4 more Smart Citations
“…Previous research identified some of the GDs' concerns; for example, it was found that GCs worry about the health of their GP (Boon et al, 2008) and that they do not possess the skills needed to create an alternative interaction with a GP suffering from dementia (Miron et al, 2019). The present research expands these insights and stresses that concern about successfully creating meaningful interaction is also shared by 30-to 45-year-old GCs.…”
Section: Discussionmentioning
confidence: 54%
“…For the GD, the dance puts old age in a new light and changes roles and attitudes in the relationship. These changes can lead to closeness even in situations where relations are characterized by emotional distance (Silverstein and Xu, 2016) and endow strength to GCs with respect to fears and anxieties that old age brings up (Miron et al, 2019). The current research also emphasizes the significance of unique experiences for the GM and the GD as part of the GD's process of leave-taking from her GM and coping with the finiteness of life, and loss -an area that has not, to date, been researched.…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations